2019
DOI: 10.1080/16078454.2019.1621020
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of unstable hemoglobin Rush with thalassemia and hemoglobin E result in thalassemia intermedia

Abstract: Background: The clinical consequences and significance of many unstable hemoglobins interacting with other hemoglobinopathies remain unrecognized. Here we first explore molecular and hematological characterizations of previously undescribed compound heterozygosity states for unstable hemoglobin Rush (Hb Rush, Beta 101 Glu > Gln, HBB: c.304G > C) with Hb E and different forms of thalassemia. Methods: Hematological assays, globin gene mutation assays and β-globin gene cluster haplotype were conducted in 11 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It has been suggested that the MCV may be affected by the presence of a mildly unstable Hb, with some unstable Hbs in association with β thalassemia resulting in red cell indices consistent with thalassemia intermedia, or even thalassemia major. 16 However, the MCV for our subject was consistent with previous reports of simple heterozygotes for HBB:c.-138C>T, so it seems unlikely co-inheritance of Hb Ottawa has influenced the mild thalassemia presentation. It should be noted that Hb instability was not demonstrated for our subject during this investigation but one previous report suggested Hb Ottawa was mildly unstable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been suggested that the MCV may be affected by the presence of a mildly unstable Hb, with some unstable Hbs in association with β thalassemia resulting in red cell indices consistent with thalassemia intermedia, or even thalassemia major. 16 However, the MCV for our subject was consistent with previous reports of simple heterozygotes for HBB:c.-138C>T, so it seems unlikely co-inheritance of Hb Ottawa has influenced the mild thalassemia presentation. It should be noted that Hb instability was not demonstrated for our subject during this investigation but one previous report suggested Hb Ottawa was mildly unstable.…”
Section: Discussionsupporting
confidence: 91%
“…5 Regardless, many reports of unstable Hb variants indicate nor-mal MCV in the absence of complicating factors. 16 The β + thalassemia mutation (HBB:c.-138C>T) was identified as African in origin by Orkin et al, 11 but has also been observed in Asian Indians with the same nucleotide substitution but on a different chromosomal background as indicated by haplotype analysis, suggesting two independent mutation origins. 17 Even though the β + thalassemia allele is mild, carriers of the HBB promoter mutation tend to have relatively high values for HbA 2 [12][13] but with variable HbF levels that might be reflective of the ethnic background and haplotype of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies have demonstrated that unstable Hb Rush [β101 (G3) Glu > Gln; HBB: c.304G > c] co-inherited with Hb E or β-thalassemia increases the proportion of Hb Rush and manifests as thalassemia intermedia. However, individuals who are heterozygous for Hb Rush alone typically exhibit mild hemolytic anemia [ 16 ]. It has also been shown that unstable Hb-Haná [β63 (E7) His > Asn; HBB: c.190 C > A] alone generally does not cause hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic mutation disrupts normal hemoglobin production (Hemoglobin A). Therefore, the low levels of hemoglobin and the high rate of red blood cell damage lead to symptoms of anemia (thalassemia) (Huang et al, 2019).…”
Section: Table (3) and Figure (1) Show The Correlations Among The Hb ...mentioning
confidence: 99%